Effect of incineration ash leachates on the hydraulic conductivity of bentonite-polymer composite geosynthetic clay liners. (15th February 2022) - Wireko, Christian; Abichou, Tarek; Tian, Kuo; Zainab, Binte; Zhang, Zhiming
Highlights: Bentonite-polymer composite geosynthetic clay liners (BPC GCLs) may contain water-soluble (linear) or water-insoluble (crosslinked) polymers. Generally, BPC GCLs with high initial polymer loading had relatively lower hydraulic conductivity than those with low initial polymer loading. For BPC GCLs containing linear polymer, polymer elution occurred when permeated with water or leachate. There was no correlation between the percentage of polymer retained and final hydraulic conductivity of the BPC GCLs containing linear polymer. Abstract: A study was conducted to evaluate the hydraulic conductivity ( k ) of six bentonite-polymer composite (BPC) geosynthetic clay liners (GCLs) using five synthetic municipal solid waste incineration ash (IA) leachates with ionic strength ( I ) ranging from 174 to1978 mM. The BPC GCLs contained a dry blend of bentonite and proprietary polymers and had polymer loading ranging from 0.5 to 5.5%. The polymers used in the BPC GCLs were classified as linear polymer (LP) or crosslinked polymer (CP) based on the swelling characteristics of specimens extracted from the GCLs. Comparable hydraulic conductivity tests were also performed on two conventional bentonite (CB) GCLs as controls. The BPC GCLs had k of 2.6 – 6.7 × 10 -11 m/s when permeated with IA leachate with I = 174 mM, whereas the CB GCLs had k > 5.0 × 10 -8 m/s when permeated with the same leachate. However, k of the BPC GCLs ranged from the order of 10 -10 to 10 -7 m/s when permeated with IA leachates with I > 600 mM. BPC GCLs with high polymer loading generally had lower k compared to those with lower polymer loading when permeated with the same IA leachate, regardless of the polymer type. Polymer eluted from the BPC GCLs containing LP during permeation with DI water or IA leachate. Unlike CPs, LPs are water-soluble, therefore, they seem to easily migrate during permeation. There was no correlation between the percentage of polymer retained and the final hydraulic conductivity of the LPB GCLs used in this study.